Occurrence of Campylobacter species from broiler chickens and chicken meat in Malaysia - Sinulingga, Teguh Suranta; Abdul Aziz, Saleha; Bitrus, Asinamai Athliamai; Zakaria, Zunita; Abu, Jalila (Springer, 2020)
Campylobacter is reported as a major cause of foodborne illness worldwide. Consumption of contaminated chicken meat is considered a significant risk factor of Campylobacter infection in humans. This study investigated the occurrence of non-Campylobacter jejuni-Campylobacter coli, in broiler chickens (n = 210) and chicken meat (n = 109). The samples were collected from seven broiler chicken farms (n = 210 cloacal swabs), 11 markets (n = 84 chicken meat), and 5 supermarkets (n = 25 chicken meat) located in different districts of Selangor State. Campylobacter were isolated from cloacal swabs using the Cape Town Protocol and from meat samples using the method of Duffy et al. (2007) with some modifications for Campylobacter isolations which were reported effective in the isolation of non-C. jejuni-C. coli Campylobacter species. The isolates were identified by Gram staining for cellular morphology, wet mount for motility and biochemical tests. Confirmation of presumed Campylobacter isolates was carried out using multiplex PCR (mPCR). One hundred seven (107/210) or 50.9% and twenty-nine (29/109) or 26.6% of chickens and chicken meat samples respectively were positive for Campylobacter species. Among the Campylobacter isolates from chickens, C. jejuni was the most predominantly isolated species (69.5%), followed by C. coli (16.2%). Campylobacter fetus and C. upsaliensis were the non-C. jejuni-C. coli Campylobacter species isolated in this study, at 9.3% and 2.5% respectively. Overall, the findings indicated broiler chickens were colonized not only by the common Campylobacter species but also by other Campylobacter species. We found the Cape Town Protocol useful to detect the occurrence of non-C. jejuni-C. coli isolates in chickens.